Corporeity and animation theater at school: hide or show (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
One of the biggest challenges encountered in teaching the performing arts is to put the student in evidence when sharing his scenic creation with colleagues, especially when the focus is usually the body. When reflecting on this aspect, the present text dealt with the possibility of the body work with students in Elementary School with the starting point in the Theater of Animation – theoretical reflection based on my Doctorate in Arts research Scenic, in progress, at the University of Brasília. This article will address the following aspects: the bodily course within the Animation Theater aimed at Elementary Schools; the body in the shade; the embodiment of the puppet with the hands; and, the body in the scene in direct animation. As methodological procedures analysis of articles, dissertations and theses were used. It was concluded that the corporeity in the puppet theater presents unique nuances to the experience in drama classes in elementary school.
Keywords: Corporeity; Animation Theater; Theater Pedagogy